Culinary MSME Development Strategy Using the Strengths, Opportunities, Aspirations, and Results (SOAR) Approach - Maulia, Tria Rizki; Qarni, Waizul; Syakir, Ahmad (Moneter: Jurnal Keuangan dan Perbankan, 2025)
Based on data from the Ministry of Cooperatives and SMEs of the Republic of Indonesia, the Economic Census from the Central Statistics Agency in 2024 showed that the large contribution of MSMEs to the Indonesian economy reached 61.07% of GDP or IDR 9,300 trillion. In addition to contributing to creating jobs, MSMEs also support local economic growth. One type of culinary MSME that is promising to be developed is the food stall business. Warung Lesehan Keluarga Mas Bambang is one of the food stalls in Medan Marelan that has many variants of food menus. This study aims to determine the right business development strategy for Warung Lesehan Keluarga Mas Bambang. This study uses a qualitative descriptive research method with SOAR analysis. The results show that the strengths of Warung Lesehan Keluarga Mas Bambang are the attractive stall design with a traditional concept, having many variants of food menus that suit the people's tongue and affordable prices. The appropriate strategies to be implemented at Warung Lesehan Keluarga Mas Bambang are the SR strategy and the OR strategy. The SR strategy is to maximize internal strategies and the OR strategy is the most strategic because it is more efficient, namely utilizing existing opportunities such as raw materials, technology, and markets. Faster impact is directly boosting revenue and image. and sustainable can be combined with SR/OA for long-term optimization.